Implementation of PAI Evaluation in the Context of Inclusive Learning - Hasniah Hasniah; Sugeng Sugeng (ALSYS, 2025)
Inclusive education requires a paradigm shift in the evaluation of Islamic Education (Pendidikan Agama Islam, PAI) learning so that it accommodates diverse student characteristics without discrimination. This study aims to analyse the concepts and principles underpinning PAI evaluation in inclusive learning, identify the challenges encountered, formulate adaptive evaluation strategies, and examine the integration of authentic assessment and differentiated instruction in PAI evaluation within inclusive classrooms. Employing a qualitative literature review, the research analyses scientific publications published between 2020 and 2025 using content analysis techniques to identify patterns, themes, and key concepts. The findings show that inclusive PAI evaluation rests on principles of fairness, flexibility, and responsiveness by integrating formative and summative assessments across cognitive, affective, and psychomotor domains through quizzes, observations, discussions, projects, and authentic evaluations that are tailored to individual student needs. Differentiated instruction emerges as a key strategy, involving adjustments to content, process, product, and learning environment, and is supported by the CIPP evaluation model. However, implementation is constrained by limited teacher competence in handling students with special needs, inadequate facilities, scarce contextual learning resources, and systemic coordination issues within institutions. The study concludes that successful inclusive PAI evaluation requires synergy in developing adaptive instruments, multi-stakeholder collaboration, and the systematic application of authentic assessments grounded in contextual learning. It recommends that the government revise the Core and Basic Competencies of PAI to integrate inclusive learning indicators, provide adequate facilities, strengthen continuous teacher training, and optimise collaboration among IRE teachers, assistant teachers, parents, and the community to realise inclusive, high-quality, and meaningful Islamic Education. Keywords: Authentic Assessment; Differentiated Instruction; Inclusive Learning; Islamic Education (PAI); Learning Evaluation